Hemispheric Processing of Chinese Scientific Metaphors: Evidence via Hemifield Presentation - Huang, Min; Shen, Lexian; Xu, Shuyuan; Huang, Yanhong; Huang, Shaojuan; Tang, Xuemei (Frontiers in Psychology, 2022)
The role of the two hemispheres in processing metaphoric language is controversial. In order to complement current debates, the current divided visual field (DVF) study introduced scientific metaphors as novel metaphors, presenting orientation mapping from the specific and familiar domains to the abstract and unfamiliar domains, to examine hemispheric asymmetry in metaphoric processing. Twenty-four Chinese native speakers from science disciplines took part in the experiment. The participants were presented with four types of Chinese word pairs: scientific metaphors, conventional metaphors, literal word pairs, and unrelated word pairs. The first word in each pair was presented centrally, and the second was presented to the left visual field (the Right Hemisphere) or the right visual field (the Left Hemisphere). Event-related potentials (ERPs) were recorded when participants read the target words and judged whether words in each pair were related. The data demonstrated that both hemispheres were involved at the initial stage of metaphor processing, but the right hemisphere took a more privileged role. The significant activation of the left hemisphere for scientific metaphoric processing supports the fine-coarse coding hypothesis. During right-visual-field presentation, the left hemisphere, responsible for the processing of closely related domains, has to integrate the loosely associated domains of scientific metaphor, which greatly increased cognitive taxes. Moreover, the data of late positive components (LPCs) revealed different hemispheric activation between scientific metaphors and conventional metaphors. Compared with literal pairs, conventional metaphors elicited significantly higher LPCs during right visual field presentation, while the scientific metaphor elicited significantly lower LPCs during left visual field presentation. The results suggest different processing mechanisms between novel metaphors and conventional metaphors and the special role of the right hemisphere in novel metaphoric processing at the later mapping stage.